PENGEMBANGAN LITERASI DAN KETERAMPILAN BAHASA INGGRIS SISWA SMPN 1 BOJONG MELALUI PROGRAM READING ALOUD - Noni Agustina; Ratnawati Susanto (LPPM Institut Pendidikan Nusantara Global, 2026)
Based on the information, SMPN 1 Bojong has implemented an English Refresh program. However, students’ English skills have not shown a significant improvement. Further development of students’ English skill is still required. In addition, the principal reported that the school education report indicates that students’ literacy skills at SMPN 1 Bojong need to be improved, and students’ reading interest remains low. Furthermore, the vice principal revealed that students’ motivation to learn English is low and their English vocabulary is limited. Therefore, the community service team from Universitas Esa Unggul carried out a community service program to develop students’ literacy and English skills through a reading aloud program. This program was implemented through several stages: socialization, training, technology integration, mentoring, evaluation, and program sustainability. The results of the community service activities showed an increase of 54.51% in students’ comprehension and vocabulary. Additionally, students expressed positive perceptions of the training, stating that they enjoyed it because the training was well designed, interesting, easy to understand, and able to increase their self-confidence.